2021
DOI: 10.1007/s41745-021-00255-z
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Developments in Graphical Pangenomics

Abstract: Pangenomes are organized collections of the genomic information from related individuals or groups. Graphical pangenomics is the study of these pangenomes using graphical methods to identify and analyze genes, regions, and mutations of interest to an array of biological questions. This field has seen significant progress in recent years including the development of graph based models that better resolve biological phenomena, and an explosion of new tools for mapping reads, creating graphical genomes, and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 82 publications
0
8
0
4
Order By: Relevance
“…As stated above, the higher breakpoint imprecision for long-read SVs might also increase (50-60%;de Boer et al, 2007). We can expect that these features also impact pangenome-based mapping and genotyping to some extent, especially repeats (Chen et al, 2019;Outten & Warren, 2021).…”
Section: Multiplatform Variant Detection and Pangenome-based Approach...mentioning
confidence: 87%
“…As stated above, the higher breakpoint imprecision for long-read SVs might also increase (50-60%;de Boer et al, 2007). We can expect that these features also impact pangenome-based mapping and genotyping to some extent, especially repeats (Chen et al, 2019;Outten & Warren, 2021).…”
Section: Multiplatform Variant Detection and Pangenome-based Approach...mentioning
confidence: 87%
“…In contrast to adding genetic variations to the reference genome [67] , Sirén et al demonstrated an alternative strategy to genotype a new sample by tracing haplotype paths through the sequence graph [64] . They developed Giraffe, a haplotype-aware pangenome mapper that prioritizes alignments under supervision from known haplotypes to avoid search-space explosion caused by combinations of biologically unlikely alleles [43] , [44] , [49] , [64] , [70] . On average, it took about 194 CPU hours to genotype a sample with a median coverage of 20× by the combination of toil-vg [71] and Giraffe [64] .…”
Section: Population-scale Structural Variation Studies Using a Hybrid...mentioning
confidence: 99%
“…The main advantage of pan-genomic approaches is that they can more accurately represent the complex variability of the genome [22] and improve genotyping of nested SVs in complex genetic backgrounds [4] , [64] . However, there is still an urgent need for efficient tools to construct complex graphs and perform sequence-to-graph alignments [42] , [43] , [44] . In the following sections, we summarize the characteristics of graph-based genotypers.…”
Section: Genotyping Structural Variation In Pan-genome Graphsmentioning
confidence: 99%
See 2 more Smart Citations